2021
DOI: 10.48550/arxiv.2109.04696
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kinematic footprint of the Milky Way spiral arms in Gaia EDR3

Luis Martinez-Medina,
Angeles Pérez-Villegas,
Antonio Peimbert

Abstract: The Milky Way spiral arms are well established from star counts as well as from the locus of molecular clouds and other young objects, however, they have only recently started to be studied from a kinematics point of view. Using the kinematics of thin disc stars in Gaia EDR3 around the extended solar neighbourhood, we create x-y projections coloured by the radial, residual rotational, and vertical Galactocentric velocities (U, ∆V, W ). The maps are rich in substructures and reveal the perturbed state of the Ga… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…For example, Castro-Ginard et al (2021) using the most updated catalogue of open clusters measured different pattern speeds for different spiral arms, favouring a flocculent structure with transient arms that co-rotate with the disc. Alternatively, Martinez-Medina et al (2021), studying the kinematics of selected stars in the Gaia EDR3 sample, found instead that stars do not always co-rotate with the disc: objects in the spiral arms tend to rotate more slowly than objects in the inter-arm region.…”
Section: Discussion: the Milky Way A Grand-design Or Flocculent Spira...mentioning
confidence: 99%
“…For example, Castro-Ginard et al (2021) using the most updated catalogue of open clusters measured different pattern speeds for different spiral arms, favouring a flocculent structure with transient arms that co-rotate with the disc. Alternatively, Martinez-Medina et al (2021), studying the kinematics of selected stars in the Gaia EDR3 sample, found instead that stars do not always co-rotate with the disc: objects in the spiral arms tend to rotate more slowly than objects in the inter-arm region.…”
Section: Discussion: the Milky Way A Grand-design Or Flocculent Spira...mentioning
confidence: 99%